2019
DOI: 10.1155/2019/8469739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-Month Resistance Training on Changes in Abdominal Adipose Tissue and Metabolic Variables in Patients with Prediabetes: A Randomized Controlled Trial

Abstract: Objective To examine the effects of resistance training relative to aerobic training on abdominal adipose tissue and metabolic variables in adults with prediabetes. Methods 105 participants with prediabetes were randomized into the resistance training group (RT, n = 35), aerobic training group (AT, n = 35), and control group (CG, n = 35). The participants completed supervised 12-month exercise; the control group followed the primary lifestyle without exercise intervention. The primary outcomes were visceral ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 24 publications
(28 reference statements)
0
33
0
Order By: Relevance
“…short-term push-ups) can reduce more abdominal subcutaneous adipose tissue than aerobic or anaerobic exercise alone 42 44 . In addition, the reduction of liver and visceral fat amounts might not differ with regard to the intensity and dose of aerobic exercise which the participants received 45 , and an increase of skeletal muscle mass was observed only in those taking anaerobic (resistant) exercise 45 . It is possible that MHO individuals might frequently receive more combined aerobic and anaerobic exercise training than the MUO and MHL so that MHO individuals had greater muscular strength than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…short-term push-ups) can reduce more abdominal subcutaneous adipose tissue than aerobic or anaerobic exercise alone 42 44 . In addition, the reduction of liver and visceral fat amounts might not differ with regard to the intensity and dose of aerobic exercise which the participants received 45 , and an increase of skeletal muscle mass was observed only in those taking anaerobic (resistant) exercise 45 . It is possible that MHO individuals might frequently receive more combined aerobic and anaerobic exercise training than the MUO and MHL so that MHO individuals had greater muscular strength than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance exercise has also been shown to improve markers of cardiovascular health (e.g., LDL cholesterol and blood pressure) [278,279], glycemic control (lower HbA1c and improved insulin sensitivity) [280,281], functional capacity [282,283], bone mineral density [284,285], body composition [283,286], sleep [287], and cognitive performance [288]. It should also be noted that regular exercise is known to improve immune function, a faculty that is particularly important in times of pandemic [126][127][128].…”
Section: Countermeasures To Prevent Sarcopenia During Covid-19mentioning
confidence: 99%
“…Currently, the effectiveness of RT for reducing VF is uncertain, and has been somewhat inconsistent across studies. In this regard, some studies have shown that RT effectively reduced VF, 40–42 but other studies did not indicate significant reductions in VF following RT 43,44 . In addition, in a 2012 systematic review and meta‐analysis by Ismail and colleagues that included 14 interventions in participants with obesity, overweight and normal weight, RT did not induce a reduction in VF and significant heterogeneity among studies was reported ( I 2 = 61.7%) 31 .…”
Section: Introductionmentioning
confidence: 99%